درجة استخدام مديري مدارس منطقة مبارك الكبير بدولة الكويت للإدارة بالمواهب من وجهة نظر المعلمين فيها - الفضلي، ياسمين هداد فاضل; المطيري، نايف لافي (جامعة جرش, 2024)
هدفت الدراسة إلى قياس درجة استخدام مديري مدارس منطقة مبارك الكبير بدولة الكويت للإدارة بالمواهب من وجهة نظر المعلمين فيها، ولتحقيق هدف الدراسة، تم استخدام المنهج الوصفي المسحي حيث تم تطوير استبانة بواقع (20) فقرة، وتم التأكد من صدقها وثباتها، ومن ثم تم توزيعها على عينة عشوائية بسيطة مكونة من (350) معلما ومعلمة. أظهرت نتائج الدراسة أن درجة استخدام مديري مدارس منطقة مبارك الكبير بدولة الكويت للإدارة بالمواهب من وجهة نظر المعلمين فيها كانت بدرجة ضعيفة، وتواجه مجموعة من المعوقات، من أهمها انشغال الإدارات المدرسية في الأعمال الإدارية، وافتقار التواصل والحوار بين المدير والمعلم، وانحسار اهتمام مديري المدارس على إتمام الحصة الدراسية بالشكل المطلوب. وفي ضوء نتائج الدراسة اقترح الباحثان مجموعة من التوصيات من أهمها: تقديم الحوافز المادية والمعنوية للمعلمين الموهوبين بالتعاون مع وزارة التربية والتعليم لما ينعكس على الموهوبين من انتماء واستمرارية. The present study aims at identifying the degree of use to which the principals of schools in Mubarak Al-Kabeer region in the State of Kuwait are used for management talents from the teachers’ perspective, To achieve this study, the descriptive approach was used, where a questionnaire was developed with (20) paragraphs, and its validity and stability was verified, The study population consisted of (9027) teachers', The questionnaire was distributed to the study sample of (360) male and female teachers in Mubarak Al-Kabeer schools. The results of the study revealed that the degree of use to which the principals of schools in Mubarak Al-Kabeer region in the State of Kuwait are used for management talents from the teachers perspective with a low degree, It faces a number of obstacles, the most important of which are the school administrations' preoccupation with administrative work, the lack of communication and dialogue between the principal and the teacher, and the declining interest of school principals in completing the lesson as required. In light of these results, the study recommended the Providing material and moral incentives for talented teachers in cooperation with the Ministry of Education, as it reflects on the talented’s affiliation and continuity. The Ministry of Education provides effective training opportunities for the gifted to develop their abilities and skills. Employing the media in the Ministry of Education through marketing the talented and spreading a culture of excellence and creativity.
Keywords: الإدارة المدرسية -- المهارات القيادية -- إدارة المواهب البشرية -- معلمو المدارس -- الكويت